Cancer morbidity in ulcerative colitis. Issue 6 (June 1982) - Prior, P; Gyde, S N; Macartney, J C; Thompson, H; Waterhouse, J A; Allan, R N
Abstract : Cancer morbidity at all sites has been studied in a series of 676 patients with ulcerative colitis under long-term review, of whom more than two-thirds had extensive disease, and the level and pattern of risk over time examined. Age-, sex-, and site-specific incidence rates were used to compute the number of cancers that might have been expected to occur. A highly significant excess of cancers was observed overall but the excess was due entirely to cancers of the digestive system. In women there was no excess or deficit of cancers outside the digestive system. In men there was a small deficit of cancers of the respiratory system. An overall 11-fold excess colorectal cancer risk was found in the series compared with that in a relevant general population after patient-years at risk had been corrected for surgical resection and patients with colorectal cancer at their first referral had been corrected for surgical resection and patients with colorectal cancer at their first referral had been excluded. When these data were expressed in an actuarial form the cumulative probability of developing colorectal cancer in the series was 8% (3.5-13%) at 25 years, after the diagnosis of ulcerative colitis had been established. The relative risk of developing colorectal cancer was highest in those patients developing colitis before the age of 30 years, and the relative risk fell as the age at diagnosis of their colitis increased. The pattern of risk of colorectal cancer over time suggests that there is an association between cancer and colitis in susceptible individuals and that the level of risk is related to age at onset of colitis.